Design and Development of the 3D Game "Catch Banana" Using Scratch 3 - Nasrullah, Nasrullah (Gameology and Multimedia Expert, 2024)
The game Catch Banana is designed using the Scratch 3D application as an interactive entertainment medium that educates users in the use of information technology. The game features a main character, a monkey, whose task is to catch as many bananas as possible with only one life. Each banana caught provides additional points, and players must reach a certain score to advance to the next level. This study aims to evaluate the effectiveness of the game as a medium of entertainment and learning for various age groups. The evaluation results indicate that Catch Banana provides an engaging and educational playing experience, successfully enhancing users' skills in using the Scratch 3D application.